Japanese presence in Djibouti - Fadel, Dr. Fatima Hussein (Thi Qar Arts Journal, 2022)
Features of change and developments appeared in the Japanese security and defense policy at the beginning of the twenty-first century, as Japan exceeded the restrictions it had committed to for decades. Which appeared off the coast of Somalia for the years (2008-2011), which the Japanese government took as a means to make gradual changes in its security and defense policy and succeeded in legislating laws and decisions aimed at strengthening the Self-Defense Forces and developing their capabilities and arming them, as well as expanding the construction of its base in Djibouti, which indicates the intentions The Japanese government maintained its military presence (the Self-Defense Forces) in Djibouti, despite the decline in piracy.